2011
DOI: 10.1111/j.1741-2358.2011.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation of oral malodour and related factors in community‐dwelling elderly Thai

Abstract: Daily variation of oral malodour and related factors in community-dwelling elderly ThaiObjectives: The purposes of this study were (i) to estimate the prevalence of oral malodour, (ii) to evaluate the daily variation of oral malodour and (iii) to assess associations of volatile sulphur compound (VSC) concentrations with socio-demographics, health behaviours and oral health status in communitydwelling elderly Thai. Methods: The subjects were 428 dentate elderly people (67.6 ± 5.6 years) living in Phitsaulok, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…Studies demonstrating that periodontitis is associated with intra-oral halitosis are consistent with our finding that improvement of periodontal conditions also results in the reduction of intra-oral halitosis (Miyazaki et al 1995, Morita & Wang 2001, Liu et al 2006, Samnieng et al 2012. The results from Paper III are consistent with other studies demonstrating reductions of VSC levels shortly after non-surgical periodontal therapy (≤4 weeks) (Quirynen et al 1998, Kara et al 2008, Tsai et al 2008, Takeuchi et al 2010.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Studies demonstrating that periodontitis is associated with intra-oral halitosis are consistent with our finding that improvement of periodontal conditions also results in the reduction of intra-oral halitosis (Miyazaki et al 1995, Morita & Wang 2001, Liu et al 2006, Samnieng et al 2012. The results from Paper III are consistent with other studies demonstrating reductions of VSC levels shortly after non-surgical periodontal therapy (≤4 weeks) (Quirynen et al 1998, Kara et al 2008, Tsai et al 2008, Takeuchi et al 2010.…”
Section: Discussionsupporting
confidence: 92%
“…Quirynen et al (2009) reported gingivitis to be the cause in 4 % of cases and periodontitis in 7 % of cases. Gingival bleeding and periodontal pockets have been associated with high levels of MM (Samnieng et al 2012). High levels of MM and H 2 S were also reported in periodontitis patients by Yaegaki & Sanada (1992 a,b).…”
Section: Periodontal Conditions and Intra-oral Halitosismentioning
confidence: 67%
See 3 more Smart Citations